Digitalizare în asistență socială: provocări, limite și direcții de dezvoltare - Rădăcină, Oana-Elena (Calitatea Vieții, 2023)
Ever since the beginning of social work as a profession, this field has leaned towards personalized face-to-face relationships with individuals, working groups, families, and communities. Social workers have permanently sought to adapt their strategies to the social context, widening their area of influence, in order to meet social needs as they arise, by integrating technological resources into professional activities. In the context of digitalization, the professional relationship of the social worker with beneficiaries faces new challenges, constraints, and directions of development. This paper aims to highlight these aspects based on relevant national and international literature reviews.